2021
DOI: 10.1159/000516670
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics, Management, and Case-Fatality of Patients Hospitalized for Stroke with a Diagnosis of COVID-19 in France

Abstract: <b><i>Introduction:</i></b> COVID-19 was found to be associated with an increased risk of stroke. This study aimed to compare characteristics, management, and outcomes of hospitalized stroke patients with or without a hospital diagnosis of CO­VID-19 at a nationwide scale. <b><i>Methods:</i></b> This is a cross-sectional study on all French hospitals covering the entire French population using the French national hospital discharge databases (<i>Programme de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…However, a sensitivity analysis where symptomatic stenosis was defined as the presence of an IS or TIA coded as primary diagnosis on the first unit of the carotid intervention stay or coded in previous stays in 60 days before the carotid intervention stay led to similar results. Moreover, the identification of stroke and TIA in the PMSI by ICD-10 codes was previously validated and this method has been used in published studies 26 , 27 , 28 . Second, the results concerning TFCAS must be interpreted with caution because of the low number performed annually in France.…”
Section: Discussionmentioning
confidence: 99%
“…However, a sensitivity analysis where symptomatic stenosis was defined as the presence of an IS or TIA coded as primary diagnosis on the first unit of the carotid intervention stay or coded in previous stays in 60 days before the carotid intervention stay led to similar results. Moreover, the identification of stroke and TIA in the PMSI by ICD-10 codes was previously validated and this method has been used in published studies 26 , 27 , 28 . Second, the results concerning TFCAS must be interpreted with caution because of the low number performed annually in France.…”
Section: Discussionmentioning
confidence: 99%
“…Data from the Global COVID-19 stroke registry comprising 853 stroke/COVID cases from a total of 15,128 strokes showed that apart from the male predominance among stroke/COVID patients mentioned before, male patients more frequently underwent endovascular therapies (58% among the endovascular-therapies-only patients with COVID-19 vs. 48.5% among controls, p-value <0.001) [ 24 ]. Likewise, in the aforementioned French study by Gabet et al, men underwent MT more frequently than women (66% vs. 48%, respectively, p=0.02) [ 22 ]. Finally, in a European multi-center cohort study conducted between March 1, 2020, and May 5, 2020, MT registry of 93 stroke/COVID patients (out of 855 total stroke patients who received MT) showed a higher representation of males in this cohort (67.7%), without, however, including any form of comparison to contemporary or historical controls [ 23 ].…”
Section: Reviewmentioning
confidence: 92%
“…To explore differences in gender-specific frequencies of stroke in patients with COVID-19, we assessed evidence from studies in which researchers compared cohorts of patients with stroke/COVID to properly matched either (i) historical cohorts, i.e., pre-pandemic stroke patients of the previous year(s) [ 14 , 17 , 20 ], and/or (ii) contemporary cohorts of patients with stroke but no COVID-19 [ 18 , 19 , 21 , 22 ]. Harrison et al performed a retrospective cohort study using electronic records from 50 healthcare organizations in the USA.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations